"How Negative Becomes Less Negative": Understanding the Effects of Comment Valence and Response Sidedness in Social Media. (13th January 2016) - Rim, Hyejoon; Song, Doori
Abstract : This study explores the influence of the public's negative comments regarding a corporate social responsibility (CSR) campaign in social media and how to best respond to them. It examined the interaction effects of comment valence and the company's response sidedness on the public's attitudes as mediated by the perceived negativity and perceived altruism. Results revealed that 2‐sided CSR responses are more effective than 1‐sided responses in enhancing altruistic motives for CSR, reducing perceived negativity in the public's comments, and eliciting favorable attitudes, especially when comments were negative. The effects of message sidedness disappeared when the public's comments were positive. Results also showed that perceived altruism and negativity mediate the effects of message strategies on the public's attitudes toward the company.